A new eco-friendly methodology for the determination of Amaranth dye in foodstuffs using diffuse reflectance spectroscopy. Issue 20 (10th May 2016) - Rossini, Eduardo Luiz; Milani, Maria Izabel; Pezza, Leonardo; Pezza, Helena Redigolo
Abstract : A green analytical methodology was developed employing diffuse reflectance spectroscopy for the analysis of amaranth in foodstuffs without clean-up steps. Abstract : A simple, fast, low cost, and environmentally friendly analytical methodology was developed for the determination of Amaranth dye in foodstuff samples, offering low consumption of reagents. Spot tests were performed using diffuse reflectance spectroscopy measurements at 530 nm of Amaranth dye on the surface of a qualitative filter paper as the solid support. Caramel coloring, an interferent in the analysis, was eluted from the spot test using aliquots of acid buffer. The calibration curve of absorbance ( A R ) as a function of the square root of the dye concentration ([Amaranth] 1/2 ) was described by: A R = −0.0176 + 14.556 [Amaranth] 1/2 ( R 2 = 0.999). The proposed method showed a linear range of 1.00 × 10 −5 to 5.00 × 10 −4 mol L −1 and detection and quantification limits of 1.13 × 10 −6 and 1.25 × 10 −5 mol L −1, respectively. The technique was applied for the determination of Amaranth in foodstuff samples and the results were consistent with those obtained by a comparative method.